Statistics super review (Super review., 2014)
This Super Review can be used as a supplement to your high school or college textbook, or as a handy guide for anyone who needs a fast review of the subject. Comprehensive, yet concise coverage -- review covers the material that students must know about statistics. Each topic is presented in a clear and easy-to-understand format that makes learning easier. Questions and answers for each topic -- let you practice what you've learned and build your statistics skills. End-of-chapter quizzes -- gauge your understanding of the important information you need to know, so you'll be ready for any homework assignment, quiz, or test.